VULNERABLE TO SUSTAINABLE ECONOMY OF COASTAL COMMUNITY IN NORTH MINAHASA - Rinny Cherill Rantung; Abraham Leslie Petir Lelengboto (Klabat Journal of Management, 2022)
Governments throughout countries in the world have developed many sustainability programs, but the development of sustainability initiatives may have an impact only when measured on a regional basis. The economic division between different islands and geographical zones in Indonesia is still evident which needs to be considered. This study aims to explore the challenging factors that the vulnerable community in North Minahasa are facing to have economy sustainability. This study uses both qualitative and quantitative approaches. A qualitative technique with in-depth interview of 59 villagers to uncover the variables needed for the questionnaire, after that, the transcription was examined using the content analysis technique, then transformed into survey questions. A valid questionnaire was given to 200 respondents and the respondent was selected by an enumerator conveniently from 2 Villages in North Minahasa which are Tiwoho, Budo. Financial Management Skill is the challenging factor contributes most to a sustainable economy in North Minahasa Region. Market Accessibility is the second factor that need to be considerate. Compare between income Financial Management skills, Business Condition, Financial Risk tolerance, Financial Accessibility, Entrepreneurial Mindset, and Financial Usability has a significant difference between income. The higher their income, they tend to have better financial skills. Keywords: Coastal Community, Sustainability Economy, Financial Management Skill, Market Accessibility.